Oxygen Aspects on Sensing and Utilization - Moriyama T; Sten GE (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Oxygen is known to be one of the strongest electron acceptors and has one of its main functions in the electron transport chain producing ATP and heat, so important for energy expenditure and thermoregulation. However, some important mechanisms of oxygen functions are not completely delineated, yet. Sensing oxygen is purposeful and serves various specific functions. One mode of action is to initiate afferent neuronal activity which requires increased cytosolic Ca2+ concentrations. Another action is linked to the Hypoxia Inducible Factor, HIF-1, which in the normoxic state is produced in a prolyl-hydroxylase regulated reaction. The calcium generated neuronal response is usually described as a quick, acute, response that is set in action within seconds whereas the HIF related responses are slower, chronic, activated after several minutes to hours. Traditionally, it has been the opinion that oxygen can diffuse freely across plasma membranes. However, the lipid bilayer has higher viscosity than water by several times, and high oxygen permeability has not been proven. Hence, oxygen transportation across plasma or cell membranes cannot be explained by diffusion alone. It is therefore justified to ask the question if a specific oxygen channel or transport mechanism remains to be discovered.